Influence of Infectious Disease Physician Approval on Appropriateness of PICC Use and Outcomes. (October 2020) - Vaughn, Valerie M; O'Malley, Megan; Flanders, Scott A.; Gandhi, Tejal N.; Petty, Lindsay A.; Malani, Anurag; Weinmann, Allison; Horowitz, Jennifer; Chopra, Vineet
Abstract : Background: Peripherally inserted central catheters (PICCs) are frequently used to deliver intravenous (IV) antibiotic therapy after discharge from the hospital. Infectious disease (ID) physicians are often consulted prior to PICC placement, but whether their approval influences PICC appropriateness and complications is not known. Methods: Using data from the Michigan Hospital Medicine Safety Consortium (HMS) on PICCs placed in critically ill and hospitalized medical patients between January 1, 2015, and July 26, 2019, we examined the association between ID physician approval of PICC insertion for IV antibiotics and device appropriateness and outcomes. Appropriateness was defined according to the Michigan Appropriateness Guide for Intravenous Catheters (MAGIC) as a composite measure of (1) avoiding PICC use for durations ≤5 days; (2) using single-lumen instead of multilumen catheters; and (3) avoiding PICC use in patients with chronic kidney disease (eGFR>45 mL/min). The associations between ID approval of PICC use and odds of PICC-related complications (eg, deep vein thrombosis, central-line–associated bloodstream infection, and catheter occlusion) were also assessed. Multivariable models adjusting for patient severity of illness and hospital-level clustering were fit to both outcomes. Results were expressed as odds ratios (ORs) with corresponding 95% CIs. Results: Data from 36, 594 patients who underwent PICC placement across 42 Michigan hospitals were included in the analysis. In total, 21, 653 (55%) PICCs were placed for the indication of IV antibiotics; 14, 935 (69%) of these had a documented ID consultation prior to placement, whereas 6, 718 (31%) did not. Of the 14, 935 PICCs with an ID consultation, 10, 238 (69%) had ID approval documented prior to device placement (Fig. 1). Compared to no approval, PICCs approved by ID prior to insertion were more likely to be appropriate (OR, 3.51; 95% CI, 3.28–3.77; P < .001). Specifically, approval was associated with higher single-lumen use (OR, 5.13; 95% CI, 4.72–5.58; P < .001), less placement of PICCs with dwell times ≤ 5 days (OR, 0.29; 95% CI, 0.25–0.32; P < .001), and less frequent use in patients with chronic kidney disease (OR, 0.80; 95% CI, 0.73–0.87; P < .001). ID approval of PICCs prior to insertion was associated with a significantly lower odds of PICC-related complications (OR, 0.57; 95% CI, 0.51–0.64) (Table 1). Conclusions: ID approval of PICC use for IV antibiotic therapy in hospitalized patients was associated with greater appropriateness and fewer complications. Policies aimed at ensuring ID review prior to PICC use may help improve patient and device safety. Funding: None Disclosures: Valerie M. Vaughn reports contract research for Blue Cross and Blue Shield of Michigan, the Department of Veterans' Affairs, the NIH, the SHEA, and the APIC. She also reports fees from the Gordon and Betty Moore Foundation Speaker's Bureau, the CDC, the Pew Research Trust, Sepsis Alliance, and The Hospital and Health System Association of Pennsylvania.